2018
DOI: 10.13045/jar.2018.00248
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on Combined Traditional Korean Medicine Treatment of Cervical Radiculopathy Patients Who Underwent Ineffective Epidural Steroid Injection Treatment

Abstract: This retrospective study reports the effects of combined traditional Korean treatment of cervical radiculopathy in patients who underwent ineffective epidural steroid injection treatment. This study analyzed cervical radiculopathy in patients who visited traditional Korean medicine hospital following an ineffective epidural steroid injection. There were 29 cases included in this study. Scores for Visual Analog Scale (VAS) and Neck Disability Index (NDI) were measured before and after combined treatment with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Now controversial, previous guidelines based upon uncontrolled trials recommended epidural steroid injections to treat spinal stenosis pain. [1][2][3][4][5][6][7][8][9][10][11] These studies led to a 271% increase from 1991 to 2011 in physician use of epidural injections to treat spinal stenosis pain and a considerable cost increase from $24 million to $174 million 12 . Friedly and colleagues 12 , re-examined these recommendations and conducted a large, randomized, controlled trial that found no statistically significant difference at six weeks for epidural glucocorticoid plus local anaesthetic injection versus epidural local anaesthetic injection only.…”
Section: Introductionmentioning
confidence: 99%
“…Now controversial, previous guidelines based upon uncontrolled trials recommended epidural steroid injections to treat spinal stenosis pain. [1][2][3][4][5][6][7][8][9][10][11] These studies led to a 271% increase from 1991 to 2011 in physician use of epidural injections to treat spinal stenosis pain and a considerable cost increase from $24 million to $174 million 12 . Friedly and colleagues 12 , re-examined these recommendations and conducted a large, randomized, controlled trial that found no statistically significant difference at six weeks for epidural glucocorticoid plus local anaesthetic injection versus epidural local anaesthetic injection only.…”
Section: Introductionmentioning
confidence: 99%